TLR4/NFκB-Mediated Anti-Inflammatory and Antioxidative Effect of Hexanic and Ethanolic Extracts of Curcuma longa L. in Buffalo Mammary Epithelial Cells - Insha Amin; Shahzada Mudasir Rashid; Sheikh Shubeena; Ishraq Hussain; Sheikh Bilal Ahmad; Manzoor Ur Rahman Mir; Sultan Alshehri; Sarah I. Bukhari; Tahir Maqbool Mir; Muneeb U. Rehman (Separations, 2022)
Mastitis is the commonest disease of bovines imposing a great economic setback and a drastic public health concern worldwide. Antibiotic resistance is the preliminary con of excessive antibiotics use for disease treatment. Studies validate an alarming increase in the antibiotic resistance of both humans and animals. For ages, medicinal plants have been used to treat a number of ailments in humans and animals, including mastitis. Curcuma longa, or turmeric, is the prerequisite in Indian cooking and has been used in traditional medicine for its magical properties. The rhizome of C. longa possesses significant anti-inflammatory, antibacterial, antifungal, and antioxidative properties. In the current study, we evaluated the hexanic and ethanolic extracts of C. longa for their anti-inflammatory and antioxidative potential against LPS-induced inflammation in buffalo mammary epithelial cells (BuMECs). Pretreatment with the extracts downregulated the expression of proinflammatory cytokine TNFα via the TLR4/NFκB-mediated signaling pathway. However, IL-6 was downregulated in only the hexanic C. longa-pretreated group. A significant upregulation of NRF2 mRNA expression was seen in both hexanic- and ethanolic-treated groups. A GC-MS/MS study of the extracts revealed the presence of important sesqueterpenoids and phenolics as the main bioactive phytoconstituents in the extracts. Sesqueterpenoids, such as turmerone, ar-turmerone, curlone, and atlantone, and phenols, such as guaiacol (2-Hydroxyanisole phenol, 2-methoxy), and ethyl ferulate/ethyl 4′-hydroxy-3′methoxycinnamate, were found in C. longa extracts. The protective role of C. longa in BuMECs against LPS-induced inflammation and oxidant insult might be due to the presence of bioactive compounds, such as terpenoid and phenolic compounds. However, we further propose the isolation of these phytoconstituents and their analysis using HPLC and NMR studies.